2002
DOI: 10.1074/jbc.m206849200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Integrin Function by CD47 Ligands

Abstract: CD47 (integrin-associated protein) is an integral membrane protein that is required for granulocyte and T cell recruitment to sites of infection (1, 2), and its absence on red blood cells leads to their rapid macrophage-mediated clearance (3). CD47 may also function as a costimulator to regulate T cell activation, survival, and Th1 versus Th2 differentiation (4, 5). Endogenous ligands for the extracellular domain of CD47 include the secreted protein thrombospondin-1 (TSP1) 1 and potentially other members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 54 publications
5
51
0
Order By: Relevance
“…Furthermore, a recent report has shown that treatment with a similar peptide can increase ␣ v ␤ 3 -mediated adhesion (25). However, we saw no effect of 4N1K on the binding of LIBS antibodies to OV-10 cells expressing either wild-type or IgV-GPI, either alone or with GRGDSP treatment (not shown), indicating that the peptide did not influence RGD-induced activation.…”
Section: N1k Treatment Promotes Igv-␣ V ␤ 3 Interactionsmentioning
confidence: 42%
See 2 more Smart Citations
“…Furthermore, a recent report has shown that treatment with a similar peptide can increase ␣ v ␤ 3 -mediated adhesion (25). However, we saw no effect of 4N1K on the binding of LIBS antibodies to OV-10 cells expressing either wild-type or IgV-GPI, either alone or with GRGDSP treatment (not shown), indicating that the peptide did not influence RGD-induced activation.…”
Section: N1k Treatment Promotes Igv-␣ V ␤ 3 Interactionsmentioning
confidence: 42%
“…We therefore tested the ability of 4N1K to enhance ␣ v ␤ 3 avidity by measuring OV-10 cell binding to AP3-coated plates, at coating concentrations that supported only nonspecific attachment by untreated cells. Although 4N1K has been reported to have CD47-independent effects on integrin functions in some situations (25,26), no increased binding with peptide treatment was observed for CD47-deficient cells (Fig. 3B).…”
Section: N1k Treatment Promotes Igv-␣ V ␤ 3 Interactionsmentioning
confidence: 87%
See 1 more Smart Citation
“…For both ␣4 and ␣5, it has been shown that only the processed form is present on the membrane surface of cells (16,22,23). The antibodies used in our experiment were directed against the C termini of ␣4 and ␣5 integrins (16,18,24). In RIPA lysates of human melanocytes and Mel Im cells, the processed C-terminal fragment of ␣4 integrin was detected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging each of these receptors elicits specific signals in T cells (25,27). Somatic mutants of the Jurkat T cell line lacking ␤1 integrins or CD47 have been useful to define signaling pathways mediated by these thrombospondin receptors (27,30). However, further defining how TSP1 and TSP2 regulate T cell function is limited by not knowing the identity of the HSPG receptor.…”
mentioning
confidence: 99%